Intensified Precipitation Seasonality Reduces Soil Inorganic N Content in a Subtropical Forest: Greater Contribution of Leaching Loss Than N2O Emissions. Issue 3 (4th March 2019) - Chen, Jie; Kuzyakov, Yakov; Jenerette, G. Darrel; Xiao, Guoliang; Liu, Wei; Wang, Zhengfeng; Shen, Weijun
Abstract: Soil nitrogen (N) loss has been predicted to intensify with increased global precipitation changes. However, the relative contributions of leaching and gaseous N emissions to intensified N losses are largely unknown. Thus, we simulated intensified precipitation seasonality in a subtropical forest by extending the dry season via rainfall exclusion and increasing the wet‐season storms via irrigation without changing the total annual precipitation. Extending the dry season length increased the monthly mean soil NO3 − content by 25%–64%, net N mineralization rate by 32%–40%, and net nitrification rate by 25%–28%. After adding water in the wet season, the monthly NO3 − leaching was enhanced by 43% in the relatively dry year (2013, 2, 094‐mm annual rainfall), but reduced by 51% in the relatively wet year (2014, 1, 551 mm). In contrast, the monthly mean N2 O emissions were reduced by 24% in 2013 but increased by 78% in 2014. Overall, the annual inorganic N content was decreased significantly by the precipitation changes. Decrease of soil inorganic N might be linked to the enhanced NO3 − leaching in 2013, and be linked to the increased N2 O emissions in 2014. However, in both years the annual total amount of N lost through leaching was significantly greater than that through N2 O emissions. The enhanced N2 O emissions driven by wet‐season storms were correlated with an increase in nirS abundance. Our results suggest that increased frequency of droughts and storms will decrease soil inorganic N content in warm and humid subtropical forests mainly through enhanced leaching losses. Key Points: Soil NO3 − content was increased by dry season extension and decreased by more abundant wet‐season storms in a subtropical forest The N loss caused by leaching was much greater than that through N2 O emissions Precipitation‐induced increases in net nitrification and N2 O emissions were related to increases in archaea amoA and nirS gene abundances